2017
DOI: 10.1038/s41598-017-05430-w
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Extracellular Domain of Neurotrophin Receptor p75 as a Biomarker for Amyotrophic Lateral Sclerosis in a Chinese cohort

Abstract: To comprehensively assess whether p75ECD in urine could be a candidate biomarker for ALS evaluation. Urine samples were collected from 101 ALS patients, 108 patients with other neurological disease (OND) and 97 healthy controls. 61 ALS patients were followed up with clinical data including ALSFRS-r every 6 to 12 months, 23 ALS patients died and 17 ALS patients lost touch during follow up period. Enzyme-linked immunoassay was employed to determine urine p75ECD concentration. The ALSFRS-r was employed to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Activation of the neurotrophin receptor p75 in response to the nerve growth factor released by activated astrocytes plays a role in developmental motor neuron death and neuronal injury [125]. The levels of urinary p75 ECD are increased in ALS patients compared with normal control subjects and patients with other neurological diseases such as PD and MS [126,127,128]. The levels of neurotrophin receptor p75 in tissues are upregulated also in AD, ischemic stroke, and seizure, suggesting a response to non-specific neuronal injury and cell stress [129].…”
Section: Liquid Biopsy In Sporadic Alsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the neurotrophin receptor p75 in response to the nerve growth factor released by activated astrocytes plays a role in developmental motor neuron death and neuronal injury [125]. The levels of urinary p75 ECD are increased in ALS patients compared with normal control subjects and patients with other neurological diseases such as PD and MS [126,127,128]. The levels of neurotrophin receptor p75 in tissues are upregulated also in AD, ischemic stroke, and seizure, suggesting a response to non-specific neuronal injury and cell stress [129].…”
Section: Liquid Biopsy In Sporadic Alsmentioning
confidence: 99%
“…Reduced TDP-43 levels (≤27.9 ng/mL) in CSF are associated with shorter survival times [112], while higher NEFL and pNEFH levels in the CSF and serum are associated with more rapid progression speed and poorer prognosis [117,120,123,124], and higher urinary p75 ECD levels are associated with more rapid progression [126,127,128]. Urinary p75 ECD levels increase linearly with disease progression from the time of diagnosis and are correlated with clinical disease parameters, ALS functional rating scale-revised (ALSFS-R) [120,127].…”
Section: Liquid Biopsy In Sporadic Alsmentioning
confidence: 99%
“…These finding were validated in a recent study encompassing 54 ALS patients and 45 healthy individuals (Shepheard et al., ). In a Chinese cohort, urine analysis was conducted in 101 ALS patients, 108 patients with other neurological disease (PD and MS), and 97 healthy controls (Jia et al., ). p75 ECD was again found higher in the ALS group compared with the others.…”
Section: Introductionmentioning
confidence: 99%
“…Research into immune cell metabolism in ALS is limited despite the role of the immune system in ALS pathogenesis [ 99 , 100 ]. Current literature has focused on lymphoblastoid cell lines (LCL’s), with a recent metabolic analysis performed on LCL’s obtained from patients with sporadic ALS, in addition to patients with familial mutations in FUS, SOD1 and TDP-43 [ 101 ]. Bioenergetic flux analysis showed that mitochondrial respiration was increased in all LCL ALS cell models but glycolysis (measured by extracellular acidification rate (ECAR)) was only altered in the SOD1 LCL’s.…”
Section: Glycolytic Changes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…The extracellular domain of p75 neurotrophin receptor (p75-ECD) is a potential urinary biomarker for ALS [ 101 , 102 , 103 , 104 ]. During neuronal stress and injury, the extracellular domain of the receptor can be cleaved [ 105 ].…”
Section: Glycolytic Changes In Amyotrophic Lateral Sclerosismentioning
confidence: 99%